Meningkatan Prestasi Dan Motivasi Dalam Melakukan Senam Lantai Dengan Menggunakan Permainan - yulidar yulidar (Jurnal Dedikasi Pendidikan, 2019)
Floor Gymnastics is one of the sub-subjects in the study of Physical Education of Health Sports (Penjasorkes), in conducting floor gymnastics required various mental and good skills. The problem formulation is: "Whether using whether using the game can improve the achievement and motivation of students in doing floor gymnastics in students of SMA Negeri 1 Meulaboh?. The purpose of research is to know the increase in achievement and motivation of students on floor gymnastics by using the game. The research hypothesis "by using the game can improve performance and motivation in performing floor gymnastics". This type of research is class action research. The research subject in this study is as many as 25 students. Based on the results of the processing gained on the cycle I can be described that the cognitive aspect of the cognition is due to 61%, psychomotor aspect is due to 61% while the affective aspect is due 68%. Cycle II can be explained that the learning of floor gymnastics with the methods of the games obtained the cognitive aspects of 100% complete, psychomotor aspects 100% complete and the affective aspect of 100% complete. The average survival rate between cycle I and cycle II is 16%. Hypotheses in this study were received. So through the approach of the game faces can improve the achievement and motivation of students in doing floor gymnastics in grade II students SMA Negeri 1 Meulaboh.